IDENTIFIKASI KANDUNGAN BORAKS PADA BAKSO DI KABUPATEN BULUKUMBA - Arfiani Nur; Artati (Jurnal Kesehatan Panrita Husada, 2019)
Abstrack The background of this research is that Borax is a chemical compound called sodium tetraborate (NaB407 10 H20). If dissolved in water it will become hydroxide and boric acid (H3B03). Borax is often misused as an additional ingredient not permitted in foods that are adapted to Permenkes RI No. 1168 / Menkes / Per / X / 1999 concerning food ingredients. The purpose of this study was to determine the content of borax in meatballs in the district of Bulukumba. This type of research is a laboratory experimental study using qualitative test methods. The sample of this study was that curcumin paper did not produce changes in color on curcumin paper, the color of curcumin paper remained yellow indicating that the sample did not contain hazardous borax.